2014
DOI: 10.1007/s40167-014-0014-8
|View full text |Cite
|
Sign up to set email alerts
|

Culture modulates sensitivity to the disappearance of facial expressions associated with serotonin transporter polymorphism (5-HTTLPR)

Abstract: The present research investigated an association between the serotonin transporter polymorphism (5-HTTLPR) and sensitivity to the disappearance of facial expressions cross-culturally and found, for the first time, that cultural norms and practices modulate the association. Participants watched both happy-to-neutral and sad-to-neutral movies and judged the point at which the emotional expressions disappeared. As predicted, the results showed that Japanese with the s/s genotype detected the disappearance of faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Indeed, the geneculture interaction framework has now been studied with several polymorphic sites and psychological outcomes (Ishii et al 2014b;Kim et al 2010a, b;Kitayama et al 2014). However, since the brain is an interactive system, G 9 C which consider multiple genetic influences will likely be important in the future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the geneculture interaction framework has now been studied with several polymorphic sites and psychological outcomes (Ishii et al 2014b;Kim et al 2010a, b;Kitayama et al 2014). However, since the brain is an interactive system, G 9 C which consider multiple genetic influences will likely be important in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, variation in the serotonin 1A receptor gene (5HTR1A) polymorphism rs6295 moderated a cultural difference in holistic attention (Kim et al 2010b). In addition, culture moderated the influence of serotonin transporter polymorphism (5-HTTLPR) on sensitivity to disappearance of facial expressions (Ishii et al 2014a). The Exon 3 variable number tandem repeat (VNTR) polymorphism of the D 4 receptor gene (DRD4) moderates cultural divergence on the overarching independence-interdependence social orientation (Kitayama et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While there has been increasing evidence for gene × culture interactions on human behavior and cognition [e.g., Kim et al, , Ishii et al, ; Kitayama et al, ], only a few brain imaging findings suggest gene × culture interactions on neural responses involved in cognition and emotion. By scanning participants from the same cultural group but with different cultural traits, Ma et al () reported distinct patterns of associations between interdependence and brain activities during self‐reflection in the two variants of the 5‐HTTLPR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, collectivistic cultural values are more likely to be apparent in nations with more S allele carriers [Chiao and Blizinsky, ]. Among Japanese but not Americans, S/S vs L allele carriers (including S/L and L/L genotypes) performed better during detection of the disappearance of facial expressions [Ishii et al, ], suggesting 5‐HTTLPR × culture interaction on behavioral responses to emotional stimuli. Third, recent fMRI research suggests that the 5‐HTTLPR moderates the association between cultural traits and brain activities related to cognition/emotion.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with growing body of research advocating one's psychological tendency may result from genetic and environmental interactions. More precisely these genotypes may be related to greater plasticity or environmental exposure (Belsky et al 2007(Belsky et al , 2009Obradovic and Boyce 2009;Way and Taylor 2010) which in turn "foster a more culturespecific way of behaving" (Ishii et al 2014).…”
Section: Uncertainty Avoidance and Prosocial Behaviormentioning
confidence: 99%